Simulation Investigation of an Active Vibration Protection System of an Operator of a Hand-Held Percussive Tool - Basista, Zygmunt (Engineering Transactions, 2006)
In the paper a complex model of the system operator-tool-base (OTB) has been presented. The evaluation and choice of the correct vibration isolation system of the grip of hand-held percussive tools requires a proper model of the system OTB. In the OTB model adapted in the paper, the model of the man-operator describes not only the dynamical reaction of the operator hands to vibration but also the behaviour of the operator as a system which controls the tool operation. Using this model, the necessary criteria for the assessment of the working comfort are formulated. Simulation of the model OTB with the proposed nonlinear pneumatic active vibration isolation system was done applying the Matlab-Simulink. The influence of parameter values of the vibration isolation system on the assumed comfort criteria was analyzed. The results obtained have been graphically presented.